Epidemiology of schistosomiasis in The Gambia: from human infections to intermediate snail host distribution and genetic diversity - Joof, Ebrima (2022)
Background Urogenital schistosomiasis is endemic in the eastern regions (Central River and Upper River Regions) of The Gambia, with occasional reports of intestinal schistosomiasis. Following the London Declaration for schistosomiasis control/elimination in 2012, The Gambia initiated a national schistosomiasis control programme. However, a lack of comprehensive and current information on the epidemiology of schistosomiasis in the country presents a major challenge for the implementation of the control programme. This study investigated the epidemiology of schistosomiasis in The Gambia, from human infections to intermediate snail host distribution and genetic diversity, to generate novel information required for the control of schistosomiasis in the country.